Fractional-View Analysis of Jaulent-Miodek Equation via Novel Analytical Techniques. (10th May 2022) - Zadeh, Ahmad Haji; Jacob, Kavikumar; Shah, Nehad Ali; Chung, Jae Dong
Abstract : In this article, we analyze the analytical result of fractional-order Jaulent-Miodek equations with the help of two novel methods, namely, ρ -Laplace decomposition method and ρ -Laplace variational iteration method. The achieved results are shown in a series form, which is rapidly converging. The approximate simulations were performed in absolute error to ensure that the suggested methods are accurate and reliable. The achieved results are graphically presented to confirm the validity and accuracy of the techniques. The study results reveal that the ρ -Laplace decomposition method is computationally very effective and accurate compared to ρ -Laplace variational iteration method to analyze the nonlinear system of fractional-order Jaulent-Miodek equations.